2017
DOI: 10.1111/jace.14818
|View full text |Cite
|
Sign up to set email alerts
|

Flash sintering of a three‐phase alumina, spinel, and yttria‐stabilized zirconia composite

Abstract: Three-phase ceramic composites constituted from equal volume fractions of a-Al 2 O 3 , MgAl 2 O 4 spinel, and cubic 8 mol% Y 2 O 3 -stabilized ZrO 2 (8YSZ) were flash-sintered under the influence of DC electric fields. The temperature for the onset of rapid densification (flash sintering) was measured using a constant heating rate at fields of 50-500 V/cm. The experiments were carried out by heating the furnace at a constant rate. Flash sintering occurred at a furnace temperature of 1350°C at a field of 100 V/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
4
29
0
4
Order By: Relevance
“…Evidence for the formation of phases far from equilibrium in flash experiments, continues to grow. For example, very recently, Kok et al have shown the evolution of a high alumina phase of spinel, which is outside the equilibrium regime of the phase diagram; this reaction was shown to occur within 2 or 3 seconds …”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the formation of phases far from equilibrium in flash experiments, continues to grow. For example, very recently, Kok et al have shown the evolution of a high alumina phase of spinel, which is outside the equilibrium regime of the phase diagram; this reaction was shown to occur within 2 or 3 seconds …”
Section: Introductionmentioning
confidence: 99%
“…However, most studies on the flash sintering have concentrated on single phase ceramic materials. Only a few investigations have been reported on the flash sintering of the ceramic composites …”
Section: Introductionmentioning
confidence: 99%
“…Only a few investigations have been reported on the flash sintering of the ceramic composites. [19][20][21] Yttria stabilized zirconia (YSZ) ceramics have been widely used in materials industry due to their high toughness, hardness, creep resistance, and ionic conductivity. Incorporation of a second phase in a ceramic matrix is known to improve their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia (ZrO 2 ) continuous fibers are the outstanding ultra‐high temperature thermal insulators and reinforced materials due to the characteristics of high melting point (2715°C), low thermal conductivity, and excellent mechanical strength . Generally, ZrO 2 fibers having the lengths larger than 1.0 m are defined as the continuous fibers .…”
Section: Introductionmentioning
confidence: 99%